8주간 흡기근육훈련과 태권도 수련이 흡연중년남성의 체력, CRP, 폐기능 및 등속성근기능에 미치는 영향 - 안영진; 이기성; 김태우; 손현지; 양진호; 김수연; 장창현 (Exercise science (Seoul, Korea), 2017)
PURPOSE: The purpose of this study was to compare and analyze the effects of Taekwondo training including 8-weeks inspiratory muscle training on physical fitness, CRP, pulmonary function and isokinetic muscle function of middle-aged male smokers. METHODS: 21 middle-aged male smokers were divided into 3 groups: inspiratory muscle training+Taekwondo training group (n=7), Taekwondo training group (n=7) and control group (n=7). Measurement variables were physical fitness (Body composition, muscular strength, muscular endurance, flexibility, cardiorespiratory function, balance), CRP, pulmonary function (FVC, FEV1, FEV1/FVC), and isokinetic muscle function (peak torque %BW, average power %BW). The repeated measure ANOVA was conducted to analyze the differences and interactions between groups and periods. In the case of any difference, t-test was conducted to perform post hoc test between pre and post treatment and the contrast was conducted to perform post hoc test between groups. One-way analysis of variance (ANOVA) was used between groups, and repeated measures t-test was used between groups. All significance levels were verified at .05. RESULTS: As a result, the combined exercise group also showed statistically significant changes in the physical fitness (Body composition, muscular strength, muscular endurance, flexibility, cardiorespiratory function), pulmonary function (FEV1, FEV1/FVC), and isokinetic muscle function (peak torque %BW). CONCLUSIONS: Consequently, it shows that 8 weeks Taekwondo training including inspiratory muscle training made a positive effect on fat content, muscular strength, muscular endurance, cardio respiratory fitness, R-extension in peak torque %BW in middle-aged male smokers. KCI Citation Count: 1